Early experience with a split-bolus single-pass CT protocol in paediatric trauma. Issue 6 (June 2017) - Leung, V.J.; Grima, M.; Khan, N.; Jones, H.R.
Abstract : Aim: To determine the adequacy of the split-bolus computed tomography (CT) technique in terms of vascular enhancement and solid-organ injury assessment in paediatric trauma. Materials and methods: A retrospective review was undertaken of all split-bolus trauma CT examinations performed in patients <16 years during the period from 1 January 2015 to 31 January 2016. Twelve examinations were performed in this time on patients with an age range of 2–15 years (mean 10.8) consisting of eight male and four female patients. Abdominal aortic and portal vein attenuation were measured using a region of interest tool. Results: The mean aortic attenuation was 267 HU and mean portal vein attenuation was 203 HU. Five cases of solid-organ injury were detected and the image quality was sufficient to grade the injury and guide clinical management in all cases. Discussion: Although the cohort is relatively small, good arterial and portal venous enhancement were achieved in all but one patient, where there was suboptimal portal venous opacification; however, there were no other patients in the same weight group making it difficult to determine whether this was a systematic problem or due to patient factors. Overall, these findings have reassured us locally that the current protocol should continue to be used, but the performance of the protocol will be audited continually. Highlights: Split bolus technique provides images with both arterial and venous enhancement. A single pass of the gantry reduces radiation dose compared to multi-pass trauma CT. Split bolus technique images are sufficient to grade solid organ injury.